Task Based Instruction in Teaching Speaking Skill in EFL Classroom - Safitri, Wahyuni (Universitas Hamzanwadi, 2018)
The aim of the study was to examine the effectiveness of task based instruction approach in teaching speaking skills of EFL learners. This research was a pre-experimental. It was conducted at the seventh grade of MTs Darul Aitam Jerowaru in the school year 2017-2018. The sample consisted of 25 students selected by using cluster random sampling technique. The data was collected using a speaking test. In analyzing the data, the researcher using paired sample t-test. The mean score of post-test (57.12) was higher than pre-test (34.56). The result of the paired sample t-test indicated that there was a significant difference in the mean scores between pre-test and post-test, t(df=24)= 49.59 at p< .01. Based on the finding, it can be concluded that task based instruction was significantly effective in teaching speaking skills.